Corrosion Inhibitory Ability of Ocimum Sanctum Linn (Tulsi) Rinse on Ion Release from Orthodontic Brackets in Some Mouthwashes: An Invitro Study - Patel, Roopal; Bhanat, Sheron; Patel, Dolly; Shah, Bhadra (National Journal of Community Medicine, 2014)
Introduction: In the oral environment, orthodontic appliances are exposed to potentially damaging physical and chemical agents which may cause metallic corrosion. Corrosion will occur continuously in mouth, due to release of irons with abrasion by food, liquids etc. The purpose of this study was to measure the amount of metal ion release from orthodontic brackets when kept in different mouthwashes and effect of tulsi rinse on ion release when combined with different mouthwashes. Methods: Three hundred and twenty stainless steel brackets (0.022”) were divided randomly into 8 equal groups and immersed in Mouthwash-A and, Mouthwash-B and mouthwash-C and distilled deionized water. These mouthwashes and distilled deionized water were all separately mixed with tulsi rinse and incubated at 37°C for 45 days. Nickel, Chromium, iron, copper and manganese released from the orthodontic brackets were measured with an inductively coupled plasma spectrometer. Results: Ion release in deionized water was higher (p<0.05) than in the 3 mouthwashes. Higher ion release was also found with Mouthwash-B compared with other 2 mouthwashes. There is no difference (p>0.05) in nickel, chromium, iron and copper ion release in the Mouthwash-A and Mouthwash-C. Tulsi rinse showed significant reduction (p<0.05) in all ion release in 3 mouthwashes used along with distilled deionzed water group. Conclusion: If ion release is concerned, Mouthwash-C mixed with tulsi rinse might be better option than Mouthwash-A as well as Mouthwash-B for orthodontic patients with stainless steel brackets.